EXAMINATION OF UNIVERSITY STUDENTS' FAMILY VALUES AND MARITAL RELATIONSHIP BELIEFS ACCORDING TO SOME VARIABLES (Third Sector Social Economic Review, 2024)
This study was conducted to determine the family values and marital relationship beliefs of 1075 students studying at state universities in Ankara and to examine them in terms of some variables. According to the findings obtained from the study, it was determined that 87.7% of the total 1075 participants were female and 12.3% were male students. It was determined that the participants received a minimum of 102 and a maximum of 284 points from the family values scale and the average score was 159.28±15.49. Accordingly, it can be said that the participants have a relatively positive approach within the scope of family values. On the marital relationship beliefs scale, it was determined that the participants received an average score of 42.60±10.55 with a minimum of 21 and a maximum of 101. It was concluded that the average score of the participants on the scale was significantly lower than the maximum score (105 points) and that the non-functional beliefs of young people towards marriage were low. According to the statistical analyses made to determine whether family values and marital relationship beliefs differ according to some variables, the status of many variables differs significantly in many sub-dimensions. According to the results of the research, it was understood that 21 percent of the marital relationship was predicted by family values.
Keywords: Family values; marital relationship beliefs; family values of young people; marital relationship beliefs of young people